A fiber composite material capable of achieving Class A combustion performance and preparation method thereof
By setting the resin as a mixture of oxazine monomer and oxazine catalyst, combined with specific filler combinations and process treatment, the problem of the combustion performance of fiber composite materials not meeting the standards is solved, and the A-level combustion performance and comprehensive performance are improved, meeting the safety requirements of building materials.
Patent Information
- Application Number
- CN202410936895.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-12
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-07-12
AI Technical Summary
The combustion performance of existing fiber composite materials does not meet the standards in construction applications and cannot meet the A-level standard in GB8624.
By setting the starting resin to a mixture of oxazine monomer and oxazine catalyst, the oxazine catalyst can catalyze the oxazine monomer reaction, release energy, and form a benzoxazine resin for the preparation of fiber composite materials. The composition of the resin includes benzoxazine monomer and oxazine catalyst, with a ratio of 5 to 10:7 to 8. Combined with specific filler combinations and process treatment, the combustion performance of the composite material reaches Class A.
The A-level combustion performance of fiber composite materials is achieved, while ensuring the toughness, bending strength and comprehensive performance of the material, meeting the safety requirements of building materials.
Smart Images

Figure QLYQS_1 
Figure BDA0004941593680000022 
Figure BDA0004941593680000131
Abstract
Description
Technical Field
[0001] The present invention relates to the field of composite materials and preparation methods thereof, and in particular to a fiber composite material capable of achieving Class A combustion performance and a preparation method thereof. Background Art
[0002] Fiber composite materials are lightweight and high-strength, and are widely used in aviation, navigation, military, and electronics industries. With the vigorous development of industrialization and assembly in the construction industry, new materials and technologies are constantly updated, and the application of fiber composite materials in construction has emerged. As buildings are important places for people's daily activities, the safety of their materials is the industry's primary consideration.
[0003] At present, fiber composite materials are mostly used in the form of glass fiber reinforced plastics in construction. The standard for their combustion performance is generally based on the flame retardant properties and oxygen index of plastic materials in UL94. This evaluation standard is applicable to the combustion performance of plastics and other polymer materials in the fields of electronics, electrical, aerospace, etc. According to the evaluation standard of UL94: V-2 means that after two 10-second combustion tests on the sample, the flame goes out within 60 seconds, and the burning material can fall off; V-1 means that after two 10-second combustion tests on the sample, the flame goes out within 60 seconds, and no burning material can fall off; V-0 means that after two 10-second combustion tests on the sample, the flame goes out within 30 seconds, and no burning material can fall off. However, this test method is not applicable to the safety of building materials, and the requirements are too low.
[0004] Therefore, there is an urgent need for a fiber composite material whose combustion performance reaches Class A in "Combustion Performance Classification of Building Materials and Products" GB8624. Summary of the invention
[0005] The object of the present invention is to provide a fiber composite material that can achieve Class A combustion performance. The raw material resin is set to be a mixture of an oxazine monomer and an oxazine catalyst. The oxazine catalyst can catalyze the reaction of the oxazine monomer to release energy, so as to solve the problem of substandard combustion performance of building materials in the prior art.
[0006] The present invention is implemented by the following technical solution: A fiber composite material capable of achieving Class A combustion performance, comprising the following raw materials in parts by weight:
[0007] 60-70 parts of roving, 12-22 parts of filler, 12-18 parts of benzoxazine resin;
[0008] The benzoxazine resin comprises a benzoxazine monomer and an oxazine catalyst;
[0009] The structural formula of the benzoxazine monomer is:
[0010] It should be noted that R 1 and R 2 The group type is not limited here, and can be phenyl, alkyl, aldehyde, etc., where R 2 The number of substitutions is also not limited here and can be zero (all four vacancies are hydrogen), one, two, three or four.
[0011] For example, the oxazine monomer of the embodiment of the present invention may be of the following structural formula:
[0012]
[0013] The oxazine catalyst may be a phenol catalyst or an imidazole catalyst, such as o-phenylphenol, 2,4-dimethylimidazole, and the like.
[0014] The mass fraction of the filler in the embodiment of the present invention is equivalent to the mass fraction of the benzoxazine resin, so as to reduce the combustion performance of the composite material by reducing the mass fraction of the resin. The key to the embodiment of the present invention is that the resin is set as a benzoxazine resin, and includes an oxazine monomer and an oxazine catalyst. The oxazine catalyst can effectively catalyze the curing reaction of the oxazine monomer, so that the oxazine monomer fully reacts in the curing process, releases the reaction energy in the system, and improves the flame retardant properties of the oxazine monomer, while ensuring the toughness and bending strength of the composite material, so that its combustion performance reaches Class A combustion performance.
[0015] Preferably, the mass ratio of the benzoxazine monomer to the oxazine catalyst is 5-10:7-8.
[0016] When the mass ratio of benzoxazine monomer to the oxazine catalyst is 5-10:7-8, under the temperature and speed conditions of the composite material generated by the pultrusion production process, the benzoxazine monomer and the oxazine catalyst in this ratio are more conducive to forming a composite material product that can meet the requirements of strength, hardness and combustion performance. If the benzoxazine monomer ratio is too high, it may cause incomplete curing and continuous deformation of the finished product in the later stage; if the oxazine catalyst ratio is too high, it will be cured and formed prematurely during the mold heating and molding process, so that the finished product is not produced out of the mold and the yarn breaks.
[0017] Preferably, the filler comprises montmorillonite, calcium carbonate, zinc oxide, aluminum hydroxide and silicon dioxide.
[0018] By combining the above five materials into fillers, the strength, hardness, glossiness, roughness, weather resistance, combustion performance, etc. of the system formed by the composite material can be effectively improved. Montmorillonite of a certain fineness can effectively improve the overall adhesion of the filler and improve the dispersion of other fillers and resins in the fiber; zinc oxide improves the opacity of each component in the resin liquid, slows down the stratification of different components, and can also improve the surface effect of the fiber composite material; the main function of aluminum hydroxide is to form a flame retardant effect, which can absorb the heat released by the resin in the composite material during combustion; the main function of silicon dioxide is to improve the hardness and surface gloss of the material; the role of calcium carbonate is to appropriately reduce the cost of raw materials while meeting the conditions of material hardness and surface effect.
[0019] Preferably, the mass ratio of the montmorillonite, calcium carbonate, zinc oxide, aluminum hydroxide and silicon dioxide is: 2-5:4-6:1-3:4-6:1-3.
[0020] Preferably, the raw material of the roving includes any one of basalt, carbon fiber and glass fiber or a combination of multiple materials.
[0021] Preferably, the fineness of the montmorillonite is 400-800 meshes, the fineness of the calcium carbonate is 400-600 meshes, the fineness of the zinc oxide is 400-600 meshes, the fineness of the aluminum hydroxide is 400-600 meshes, and the fineness of the silicon dioxide is 400-800 meshes.
[0022] The particle size of the filler will directly affect the physical and chemical properties of the material and the apparent effect of the composite material. Therefore, the particle size of the filler should be moderate. If the particle size is too large, the dispersion of the filler during the preparation process will be affected, which may lead to a decrease in flame retardancy and uneven hardness of the material. If the particle size is too small, although the dispersion can be improved, it will increase the viscosity of the material and affect the processing performance.
[0023] In order to better achieve the above-mentioned object, the present invention also provides a method for preparing a fiber composite material capable of achieving Class A combustion performance, comprising the following steps:
[0024] S1: Weigh filler, benzoxazine resin and release agent, mix and stir, and pour into a dipping tank;
[0025] S2: After calculating the amount of yarn according to the product cross-section, the calculated amount of untwisted roving is immersed in the dipping tank to obtain a mixed material after being fully soaked;
[0026] S3: The mixed material is subjected to a pultrusion process to obtain a composite material.
[0027] Preferably, the release agent accounts for 1-2 wt % of the benzoxazine resin.
[0028] Preferably, in the pultrusion process of S3, the starting temperature is 100°C and the molding temperature is 120°C to 200°C.
[0029] Compared with the prior art, the embodiments of the present invention have the following advantages and beneficial effects:
[0030] 1. In the embodiment of the present invention, the resin is set as a benzoxazine resin, and includes an oxazine monomer and an oxazine catalyst. The oxazine catalyst can effectively catalyze the curing reaction of the oxazine monomer, so that the oxazine monomer can fully react in the curing process, release the reaction energy in the system, and improve the flame retardant properties of the oxazine monomer, while ensuring the toughness and bending strength of the composite material, so that it can achieve Class A combustion performance.
[0031] 2. The embodiment of the present invention reduces the organic component in the composite fiber by reducing the resin component, thereby significantly improving the flame retardant properties of the composite material. More importantly, the embodiment of the present invention improves the strength, hardness, surface gloss and waterproof performance of the composite material by setting the filler as a combination of five substances and limiting the amount of the five substances, so that the composite material reaches the A2 level combustion performance of building materials, while also ensuring the comprehensive performance of the composite material.
[0032] 3. The embodiment of the present invention limits the fineness of the five filler components, improves their dispersibility while ensuring processing performance, and avoids the problems of reduced flame retardancy of the composite material and uneven hardness of the material.
[0033] In general, a fiber composite material capable of achieving Class A combustion performance provided by an embodiment of the present invention achieves Class A combustion performance by setting the raw material resin to a mixture of an oxazine monomer and an oxazine catalyst, wherein the oxazine catalyst can catalyze the reaction of the oxazine monomer and release energy. DETAILED DESCRIPTION
[0034] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.
[0035] Therefore, the detailed description of the embodiments of the present invention provided below is not intended to limit the scope of the claimed invention, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] An embodiment of the present invention provides a method for preparing a fiber composite material capable of achieving Class A combustion performance, comprising the following steps:
[0037] S1: weighing a filler, a benzoxazine resin and a release agent, mixing and stirring, and introducing the mixture into a dipping tank; the release agent accounts for 1 to 2 wt % of the benzoxazine resin;
[0038] S2: Calculate the amount of yarn according to the product cross-section, immerse the calculated amount of untwisted roving into the dipping tank, and obtain the mixed material after sufficient dipping;
[0039] S3: The mixed material is subjected to a pultrusion process to obtain a composite material.
[0040] The filler is 12 to 22 parts by weight, the oxazine resin includes a benzoxazine monomer and an oxazine catalyst, the oxazine catalyst is 7 to 8 parts by weight, the oxazine monomer is 5 to 10 parts by weight, and the roving is 60 to 70 parts by weight;
[0041] The filler comprises montmorillonite, calcium carbonate, zinc oxide, aluminum hydroxide and silicon dioxide, with the mass proportions being 2-5, 4-6, 1-3, 4-6 and 1-3 respectively; the fineness of montmorillonite is 400-800 meshes, the fineness of calcium carbonate is 400-600 meshes, the fineness of zinc oxide is 400-600 meshes, the fineness of aluminum hydroxide is 400-600 meshes, and the fineness of silicon dioxide is 400-800 meshes;
[0042] The raw materials of roving include any one of basalt, carbon fiber, glass or a combination of multiple materials.
[0043] Example 1
[0044] This embodiment provides a method for preparing a fiber composite material capable of achieving Class A combustion performance, comprising the following steps:
[0045] Weigh the following components in the following mass ratios: 65 parts of roving, 18 parts of benzoxazine resin, and 17 parts of filler. The benzoxazine resin is mixed evenly in a mass ratio of 10:7 between components A and B, wherein component A is oxazine monomer with the structural formula: Component B is an oxazine catalyst, specifically o-phenylphenol, and the filler is 400 mesh nano-montmorillonite, 600 mesh calcium carbonate, 400 mesh zinc oxide, 600 mesh aluminum hydroxide, and 400 mesh silicon dioxide, which are mixed evenly in a mass ratio of 5:4:3:6:3. The above-mixed benzoxazine resin and filler are fully stirred at a mass ratio of 18:17 at room temperature, with a stirring speed of 3000r / min and a stirring time of 15min. After the stirred emulsion is allowed to stand for 10min, it is introduced into a dipping tank. Before being introduced into the dipping tank, a release agent is added and stirred evenly. The release agent is triethanolamine oil, which accounts for 1-2wt% of the benzoxazine resin.
[0046] The untwisted roving is continuously added to pass through the preforming die to form the yarn, and the emulsion slurry obtained after stirring the powder resin is introduced into the glue dipping tank, and the yarn is immersed in the glue tank for full infiltration.
[0047] The mold is heated to 100° C., and the traction machine is started to pull the roving at a traction speed of 12 cm / min until the yarn impregnated with the slurry passes through the heated mold and completely passes through.
[0048] By observing the hardness of the material after heating and forming, the temperature is gradually increased from 100°C and the pulling speed is gradually adjusted from 12cm / min. When the temperature is adjusted to 200°C and the pulling speed is adjusted to 19cm / min, a metal hammer is used to hit the material. When a metal crisp sound is heard, the composite material is obtained.
[0049] Example 2
[0050] This embodiment provides a method for preparing a fiber composite material capable of achieving Class A combustion performance, comprising the following steps:
[0051] Weigh the following components in the following mass ratios: 65 parts of roving, 12 parts of benzoxazine resin, and 17 parts of filler. The benzoxazine resin is mixed evenly in a mass ratio of 10:7 between components A and B, wherein component A is oxazine monomer with the structural formula: Component B is an oxazine catalyst, specifically o-phenylphenol, and the filler is 800 mesh nano-montmorillonite, 400 mesh calcium carbonate, 600 mesh zinc oxide, 400 mesh aluminum hydroxide, and 800 mesh silicon dioxide, which are mixed evenly according to a mass ratio of 2:6:1:4:1. The above mixed benzoxazine resin and filler are fully stirred at a mass ratio of 18:17 at room temperature, with a stirring speed of 3000r / min and a stirring time of 25min. After the stirred emulsion is allowed to stand for 20min, it is introduced into a dipping tank. Before being introduced into the dipping tank, a release agent is added and stirred, and the release agent is triethanolamine oil, which accounts for 1-2wt% of the benzoxazine resin.
[0052] The untwisted roving is continuously added to pass through the preforming die to form the yarn, and the emulsion slurry obtained after stirring the powder resin is introduced into the glue dipping tank, and the yarn is immersed in the glue tank for full infiltration.
[0053] The mold is heated to 100° C., and the traction machine is started to pull the roving at a traction speed of 12 cm / min until the yarn impregnated with the slurry passes through the heated mold and completely passes through.
[0054] By observing the hardness of the material after heating and forming, the temperature was gradually increased from 100°C, and the pulling speed was gradually adjusted from 12 cm / min. When the temperature was adjusted to 200°C, the pulling speed was still 12 cm / min, and the material was struck with a metal hammer. When a metal crisp sound appeared, the composite material was obtained. Compared with Example 1, its forming speed was relatively slow, and the surface was relatively rougher.
[0055] Comparative Example 1
[0056] A method for preparing a fiber composite material is provided, comprising the following steps:
[0057] Weigh the mass ratio of each component: 65 parts of roving, 18 parts of polyetherimide (unsaturated polyester resin), and 17 parts of filler. Take 600 mesh nano-montmorillonite, 400 mesh calcium carbonate, 600 mesh zinc oxide, 600 mesh aluminum hydroxide, and 800 mesh silicon dioxide as fillers, and mix them evenly according to the mass ratio of 5:4:3:6:3. Stir the above mixed resin and filler at a mass ratio of 18:17 at room temperature, with a stirring speed of 3000r / min and a stirring time of 25min. After the emulsion is stirred and allowed to stand for 10min, it is introduced into the dipping tank. Before introducing it into the dipping tank, add a release agent and stir evenly. The release agent is triethanolamine oil, accounting for 1-2wt% of the resin.
[0058] The untwisted roving is continuously added to pass through the preforming die to form the yarn, and the emulsion slurry obtained after stirring the powder resin is introduced into the glue dipping tank, and the yarn is immersed in the glue tank for full infiltration.
[0059] The mold is heated to 120°C, and the traction machine is started to pull the roving at a traction speed of 12 cm / min until the yarn impregnated with the slurry passes through the heated mold and completely passes through.
[0060] By observing the hardness of the material after heating and forming, the temperature was gradually increased from 100°C and the pulling speed was gradually adjusted from 12cm / min. When the temperature was adjusted to 200°C and the pulling speed was adjusted to 24cm / min, the composite material was formed.
[0061] Comparative Example 2
[0062] A method for preparing a fiber composite material is provided, comprising the following steps:
[0063] Weigh the mass ratio of each component: 65 parts of roving, 18 parts of epoxy resin, and 17 parts of filler. Take 600 mesh nano-montmorillonite, 400 mesh calcium carbonate, 600 mesh zinc oxide, 600 mesh aluminum hydroxide, and 800 mesh silicon dioxide as fillers, and mix them evenly according to the mass ratio of 5:4:3:6:3. Stir the above mixed resin and filler at a mass ratio of 18:17 at room temperature, with a stirring speed of 3000r / min and a stirring time of 25min. After the emulsion is stirred and allowed to stand for 10min, it is introduced into the dipping tank. Before introducing it into the dipping tank, add a release agent and stir evenly. The release agent is triethanolamine oil, accounting for 1-2wt% of the resin.
[0064] The untwisted roving is continuously added to pass through the preforming die to form the yarn, and the emulsion slurry obtained after stirring the powder resin is introduced into the glue dipping tank, and the yarn is immersed in the glue tank for full infiltration.
[0065] The mold is heated to 100° C., and the traction machine is started to pull the roving at a traction speed of 12 cm / min until the yarn impregnated with the slurry passes through the heated mold and completely passes through.
[0066] By observing the hardness of the material after heating and forming, the temperature is gradually increased from 100°C and the pulling speed is gradually adjusted from 12cm / min. When the temperature is adjusted to 200°C and the pulling speed is adjusted to 19cm / min, a metal hammer is used to hit the material. When a metal crisp sound is heard, the composite material is obtained.
[0067] Comparative Example 3
[0068] A method for preparing a fiber composite material is provided, comprising the following steps:
[0069] Weigh the following components in the following mass ratios: 65 parts of roving, 10 parts of benzoxazine resin, and 17 parts of filler. The benzoxazine resin is mixed evenly in a mass ratio of 10:7 between components A and B, wherein component A is oxazine monomer with the structural formula: Component B is an oxazine catalyst, specifically o-phenylphenol, and the filler is 600 mesh nano-montmorillonite, 400 mesh calcium carbonate, 600 mesh zinc oxide, 600 mesh aluminum hydroxide, and 800 mesh silicon dioxide, which are mixed evenly in a mass ratio of 5:4:3:6:3. The above mixed benzoxazine resin and filler are fully stirred at room temperature in a mass ratio of 18:17, at a stirring speed of 3000 r / min, and for 25 minutes.
[0070] The emulsion obtained by stirring is too viscous and fails to form an emulsion, and the yarn cannot be completely wetted, so the resin component ratio is too low.
[0071] Comparative Example 4
[0072] A method for preparing a fiber composite material is provided, comprising the following steps:
[0073] Weigh the following components in the following mass ratios: 65 parts of roving, 30 parts of benzoxazine resin, and 17 parts of filler. The benzoxazine resin is mixed evenly in a mass ratio of 10:7 between components A and B, wherein component A is oxazine monomer with the structural formula: Component B is an oxazine catalyst, specifically o-phenylphenol, and the filler is 600 mesh nano-montmorillonite, 400 mesh calcium carbonate, 600 mesh zinc oxide, 600 mesh aluminum hydroxide, and 800 mesh silicon dioxide, which are mixed evenly in a mass ratio of 5:4:3:6:3. The above-mixed benzoxazine resin and filler are fully stirred at a mass ratio of 18:17 at room temperature, at a stirring speed of 3000 r / min, for 25 minutes, and the emulsion obtained by stirring is allowed to stand for 15 minutes before being introduced into a dipping tank.
[0074] The untwisted roving is continuously added to pass through the preforming die to form the yarn, and the emulsion slurry obtained after stirring the powder resin is introduced into the glue dipping tank, and the yarn is immersed in the glue tank for full infiltration.
[0075] The viscosity of the emulsion slurry is too low and the fluidity is too high. In the process from the infiltration of the yarn to the mold, most of the slurry infiltrated on the yarn has dripped off, and too little slurry remains on the yarn.
[0076] The mold is heated to 100° C., and the traction machine is started to pull the roving at a traction speed of 12 cm / min until the yarn impregnated with the slurry passes through the heated mold and completely passes through.
[0077] By observing the hardness of the material after heating and forming, the temperature is gradually increased from 100°C and the pulling speed is gradually adjusted from 12cm / min. When the temperature is adjusted to 200°C and the pulling speed is adjusted to 25cm / min, a metal hammer is used to strike the material. When a metal crisp sound is heard, the composite material is obtained. Compared with Example 1, the forming speed is relatively fast.
[0078] Example 3
[0079] This embodiment provides a method for preparing a fiber composite material capable of achieving Class A combustion performance, comprising the following steps:
[0080] Weigh the following components in the following mass ratios: 65 parts of roving, 18 parts of benzoxazine resin, and 17 parts of filler. The benzoxazine resin is mixed evenly in a mass ratio of 5:8 between components A and B, wherein component A is oxazine monomer with the structural formula:
[0081] Component B is an oxazine catalyst, specifically o-phenylphenol, and the filler is 600 mesh nano-montmorillonite, 400 mesh calcium carbonate, 600 mesh zinc oxide, 600 mesh aluminum hydroxide, and 800 mesh silicon dioxide, which are mixed evenly in a mass ratio of 5:4:3:6:3. The above-mixed benzoxazine resin and filler are fully stirred at a mass ratio of 18:17 at room temperature, at a stirring speed of 3000 r / min, for 25 minutes, and the obtained emulsion is allowed to stand for 10 minutes before being introduced into a dipping tank.
[0082] The untwisted roving is continuously added to pass through the preforming die to form the yarn, and the emulsion slurry obtained after stirring the powder resin is introduced into the glue dipping tank, and the yarn is immersed in the glue tank for full infiltration.
[0083] The mold was heated to 100°C, and the traction machine was started to pull the untwisted roving at a pulling speed of 12 cm / min. After the yarn impregnated with the slurry passed through the heated mold, it passed completely, but the impregnated yarn had slight fracture marks after traveling a distance inside the mold. The reason is that the proportion of component B is slightly higher, and an obvious stress boundary line is generated between the heated yarn and the unheated yarn, resulting in a slight fracture at this position under the action of tension.
[0084] Example 4
[0085] This embodiment provides a method for preparing a fiber composite material capable of achieving Class A combustion performance, comprising the following steps:
[0086] Weigh the following components in the following mass ratios: 65 parts of roving, 18 parts of benzoxazine resin, and 17 parts of filler. The benzoxazine resin is mixed evenly in a mass ratio of 12:7 between components A and B, wherein component A is oxazine monomer with the structural formula: Component B is an oxazine catalyst, specifically 2,4-dimethylimidazole, and the filler is 600 mesh nano-montmorillonite, 400 mesh calcium carbonate, 600 mesh zinc oxide, 600 mesh aluminum hydroxide, and 800 mesh silicon dioxide, which are mixed evenly according to a mass ratio of 5:4:3:6:3. The above-mixed benzoxazine resin and filler are fully stirred at a mass ratio of 18:17 at room temperature, with a stirring speed of 3000r / min and a stirring time of 25min. After the stirred emulsion is allowed to stand for 10min, it is introduced into the dipping tank. Before being introduced into the dipping tank, a release agent is added and stirred evenly. The release agent is triethanolamine oil, which accounts for 1-2wt% of the benzoxazine resin.
[0087] The untwisted roving is continuously added to pass through the preforming die to form the yarn, and the emulsion slurry obtained after stirring the powder resin is introduced into the glue dipping tank, and the yarn is immersed in the glue tank for full infiltration.
[0088] The mold is heated to 100° C., and the traction machine is started to pull the roving at a traction speed of 12 cm / min until the yarn impregnated with the slurry passes through the heated mold and completely passes through.
[0089] Through observation, the temperature was gradually increased from 100℃, and the pulling speed was gradually adjusted from 12cm / min. When the temperature was adjusted to 200℃ and the pulling speed was adjusted to 19cm / min, the material was formed, and the metal hammer was used to hit the material, and the metal brittleness was reduced.
[0090] Example 5
[0091] This embodiment provides a method for preparing a fiber composite material capable of achieving Class A combustion performance, comprising the following steps:
[0092] Weigh the following components in the following mass ratios: 65 parts of roving, 18 parts of benzoxazine resin, and 17 parts of filler. The benzoxazine resin is mixed evenly in a mass ratio of 10:7 between components A and B, wherein component A is oxazine monomer with the structural formula: Component B is an oxazine catalyst, specifically 2,4-dimethylimidazole, and the filler is 600 mesh nano-montmorillonite, 400 mesh calcium carbonate, and 600 mesh zinc oxide, which are mixed evenly in a mass ratio of 5:4:3. The above-mixed benzoxazine resin and filler are fully stirred at a mass ratio of 18:17 at room temperature, with a stirring speed of 3000r / min and a stirring time of 25min. After the stirred emulsion is allowed to stand for 10min, it is introduced into the dipping tank. Before being introduced into the dipping tank, a release agent can be applied to the inner wall of the dipping tank. The release agent is triethanolamine oil, which accounts for 1-2wt% of the benzoxazine resin.
[0093] The untwisted roving is continuously added to pass through the preforming die to form the yarn, and the emulsion slurry obtained after stirring the powder resin is introduced into the glue dipping tank, and the yarn is immersed in the glue tank for full infiltration.
[0094] The mold is heated to 100° C., and the traction machine is started to pull the roving at a traction speed of 12 cm / min until the yarn impregnated with the slurry passes through the heated mold and completely passes through.
[0095] By observing the hardness of the material after heating and forming, the temperature was gradually increased from 100°C, and the pulling speed was gradually adjusted from 12cm / min. When the temperature was adjusted to 200°C and the pulling speed was adjusted to 19cm / min, the material was struck with a metal hammer. The resulting composite material had no obvious metal crisp sound, a relatively loose texture, obvious surface roughness, relatively obvious pores, and no surface gloss.
[0096] Example 6
[0097] This embodiment provides a method for preparing a fiber composite material capable of achieving Class A combustion performance, comprising the following steps:
[0098] Weigh the following components in the following mass ratios: 65 parts of roving, 18 parts of benzoxazine resin, and 17 parts of filler. The benzoxazine resin is mixed evenly in a mass ratio of 10:7 between components A and B, wherein component A is oxazine monomer with the structural formula: Component B is an oxazine catalyst, specifically 2,4-dimethylimidazole, and the filler is 600 mesh nano-montmorillonite, 400 mesh calcium carbonate, 600 mesh aluminum hydroxide, and 800 mesh silicon dioxide, which are mixed evenly according to a mass ratio of 5:4:6:3. The above mixed benzoxazine resin and filler are fully stirred at a mass ratio of 18:17 at room temperature, with a stirring speed of 3000r / min and a stirring time of 25min. After the stirred emulsion is allowed to stand for 10min, it is introduced into the dipping tank. Before being introduced into the dipping tank, a release agent is added and stirred evenly. The release agent is triethanolamine oil, which accounts for 1-2wt% of the benzoxazine resin.
[0099] The untwisted roving is continuously added to pass through the preforming die to form the yarn, and the emulsion slurry obtained after stirring the powder resin is introduced into the glue dipping tank, and the yarn is immersed in the glue tank for full infiltration.
[0100] The mold is heated to 100°C, and the traction machine is started to pull the untwisted roving at a traction speed of 12 cm / min until the yarn soaked in the slurry passes through the heated mold and completely passes through. At the same time, during the operation, the emulsion in the dipping tank has a more obvious stratification phenomenon, and the turbidity of the slurry is reduced.
[0101] By observing the hardness of the material after heating and forming, the temperature was gradually increased from 100°C and the pulling speed was gradually adjusted from 12 cm / min. When the temperature was adjusted to 200°C and the pulling speed was adjusted to 19 cm / min, the surface of the obtained fiber composite material was relatively rough and its surface color was darker than that of Example 1.
[0102] Example 7
[0103] This embodiment provides a method for preparing a fiber composite material capable of achieving Class A combustion performance, comprising the following steps:
[0104] Weigh the following components in the following mass ratios: 65 parts of roving, 18 parts of benzoxazine resin, and 17 parts of filler. The benzoxazine resin is mixed evenly in a mass ratio of 10:7 between components A and B, wherein component A is oxazine monomer with the structural formula: Component B is an oxazine catalyst, specifically 2,4-dimethylimidazole, and the filler is 600 mesh nano-montmorillonite, 400 mesh calcium carbonate, 600 mesh zinc oxide, and 600 mesh aluminum hydroxide, which are mixed evenly according to a mass ratio of 5:3:4:2. The above-mixed benzoxazine resin and filler are fully stirred at a mass ratio of 18:17 at room temperature, with a stirring speed of 3000r / min and a stirring time of 25min. After the stirred emulsion is allowed to stand for 10min, it is introduced into the dipping tank. Before being introduced into the dipping tank, a release agent can be applied to the inner wall of the dipping tank. The release agent is triethanolamine oil, which accounts for 1-2wt% of the benzoxazine resin.
[0105] The untwisted roving is continuously added to pass through the preforming die to form the yarn, and the emulsion slurry obtained after stirring the powder resin is introduced into the glue dipping tank, and the yarn is immersed in the glue tank for full infiltration.
[0106] The mold is heated to 100° C., and the traction machine is started to pull the roving at a traction speed of 12 cm / min until the yarn impregnated with the slurry passes through the heated mold and completely passes through.
[0107] By observing the hardness of the material after heating and forming, the temperature was gradually increased from 100°C and the pulling speed was gradually adjusted from 12 cm / min. When the temperature was adjusted to 200°C and the pulling speed was adjusted to 19 cm / min, the surface roughness of the obtained composite material was obvious compared with that of Example 1, and the surface glossiness was significantly reduced, and the hardness of the material was reduced.
[0108] Example 8
[0109] This embodiment provides a method for preparing a fiber composite material capable of achieving Class A combustion performance, comprising the following steps:
[0110] Weigh the following components in the following mass ratios: 65 parts of roving, 18 parts of benzoxazine resin, and 17 parts of filler. The benzoxazine resin is mixed evenly in a mass ratio of 10:7 between components A and B, wherein component A is oxazine monomer with the structural formula: Component B is an oxazine catalyst, specifically 2,4-dimethylimidazole, and the filler is 600 mesh nano-montmorillonite, 400 mesh calcium carbonate, 600 mesh zinc oxide, 600 mesh aluminum hydroxide, and 800 mesh silicon dioxide, which are mixed evenly according to a mass ratio of 1:7:4:2:4. The above mixed benzoxazine resin and filler are fully stirred at a mass ratio of 18:17 at room temperature, with a stirring speed of 3000r / min and a stirring time of 25min. After the stirred emulsion is allowed to stand for 10min, it is introduced into the dipping tank. Before being introduced into the dipping tank, a release agent is added and stirred evenly. The release agent is triethanolamine oil, which accounts for 1-2wt% of the benzoxazine resin.
[0111] The roving is continuously added to the preformed mold for yarn forming, and the slurry obtained after stirring the powder resin is introduced into the dipping tank, and the yarn is immersed in the tank for full infiltration. After the stirring of the obtained slurry is stopped, the liquid and solid are slightly separated, and the solid in the slurry is not easy to adhere to the yarn.
[0112] The mold is heated to 100° C., and the traction machine is started to pull the roving at a traction speed of 12 cm / min until the yarn impregnated with the slurry passes through the heated mold and completely passes through.
[0113] By observing the heating molding, the temperature was gradually increased from 120℃, and the pulling speed was gradually adjusted from 12cm / min. When the temperature was adjusted to 200℃ and the pulling speed was adjusted to 19cm / min, after the fiber body was pulled out of the mold for a distance, the mold was blocked by part of the filler that was dried and stuck in it, and part of the filler did not come out of the mold with the fiber. When the pulling force was continued, the yarn broke slightly in the mold.
[0114] Example 9
[0115] This embodiment provides a method for preparing a fiber composite material capable of achieving Class A combustion performance, comprising the following steps:
[0116] Weigh the following components in the following mass ratios: 65 parts of roving, 18 parts of benzoxazine resin, and 17 parts of filler. The benzoxazine resin is mixed evenly in a mass ratio of 10:7 between components A and B, wherein component A is oxazine monomer with the structural formula:
[0117] Component B is an oxazine catalyst, specifically 2,4-dimethylimidazole, and the filler is 300 mesh nano-montmorillonite, 400 mesh calcium carbonate, 600 mesh zinc oxide, 600 mesh aluminum hydroxide, and 800 mesh silicon dioxide, which are mixed evenly according to a mass ratio of 5:4:3:6:3. The above-mixed benzoxazine resin and filler are fully stirred at a mass ratio of 18:17 at room temperature, with a stirring speed of 3000r / min and a stirring time of 25min. After the stirred emulsion is allowed to stand for 10min, it is introduced into the dipping tank. Before being introduced into the dipping tank, a release agent can be applied to the inner wall of the dipping tank. The release agent is triethanolamine oil, which accounts for 1-2wt% of the benzoxazine resin.
[0118] The untwisted roving is continuously added to pass through the preforming die to form the yarn, and the emulsion slurry obtained after stirring the powder resin is introduced into the glue dipping tank, and the yarn is immersed in the glue tank for full infiltration.
[0119] The mold is heated to 100° C., and the traction machine is started to pull the roving at a traction speed of 12 cm / min until the yarn impregnated with the slurry passes through the heated mold and completely passes through.
[0120] By observing the hardness of the material after heating and forming, the temperature was gradually increased from 100°C and the pulling speed was gradually adjusted from 12cm / min. When the temperature was adjusted to 200°C and the pulling speed was adjusted to 19cm / min, the surface of the generated fiber composite material was relatively rough, the surface texture of the material was unevenly dispersed, some parts were dense and shiny, and some parts were relatively loose and had holes.
[0121] Test results: The composite materials prepared in Examples 1-9 and Comparative Examples 1-4 were subjected to performance tests. The combustion performance was tested using the method described in the current national standard "Classification of Combustion Performance of Building Materials and Products" GB / T 8624, the water absorption rate was tested using the method described in the national standard "Test Method for Water Absorption of Fiber-Reinforced Plastics" GB / T 1462, the Barcol hardness was tested using the method described in the national standard "Barcol Hardness Test Method for Reinforced Plastics" GB / T 3854, and the tensile strength was tested using the method described in the current national standard "Test Method for Tensile Properties of Fiber-Reinforced Plastics" GB / T 1447. The test results are shown in Table 1 below:
[0122] Table 1
[0123]
[0124]
[0125]
[0126] Conclusion: From Table 1, we can see that:
[0127] 1. By comparing Comparative Examples 1 and 2 with Examples 1-2, it can be seen that after the resin is set as benzoxazine resin, the combustion performance of the composite material is significantly improved.
[0128] 2. Comparison of Comparative Examples 3 and 4 with Examples 1-2 shows that only when the mass fraction of benzoxazine resin is 12-18 parts, the mechanical properties and physical properties can meet the requirements while meeting the combustion performance. When the mass fraction of oxazine resin is less than 12, the slurry is too thick and the fiber cannot be infiltrated; when the mass fraction of oxazine resin is greater than 18, the calorific value of the combustion performance of the generated finished product cannot meet the A-level requirements.
[0129] 3. By comparing Example 4, Example 1, and Example 3, it can be seen that when the mass ratio of oxazine monomer to oxazine catalyst is in the range of 5-10:7-8, under the curing temperature of the resin and at a suitable production speed, the fiber composite material can be smoothly demolded and achieve the required strength; when the mass ratio is less than 5:8, the proportion of oxazine catalyst is too large, which will cause premature curing, the slurry will be blocked in the mold or at the mold entrance, and the fiber will break; when the mass ratio is greater than 10:7, the slurry cannot be fully cured in the mold, resulting in continuous curing reaction after the material is demolded, which will cause shrinkage deformation and reduce the metal brittleness.
[0130] 4. By comparing Examples 5-8 with Example 1, it can be seen that when the filler includes five components, the strength, hardness, combustion performance, apparent mass and water absorption rate of the fiber composite material can achieve good results. When the amount of nano-montmorillonite is too small, after the slurry is fully stirred and left to stand, the solid-liquid stratification is obvious, and the surface of the finished product is rough and the texture is loose. The reason is that nano-montmorillonite has a certain adsorption and gelling effect, which can effectively disperse and adsorb other fillers and form an emulsion state in the liquid; when aluminum hydroxide is lacking, the combustion performance of the material is reduced, because aluminum hydroxide can effectively absorb the heat released by the resin during the combustion process and form a dense structure to prevent further combustion; when silicon dioxide is lacking, the hardness and glossiness of the material are significantly reduced. Compared with several other fillers, silicon dioxide can effectively increase the surface hardness of the material; when zinc oxide is reduced, the turbidity of the slurry is reduced, and the resin and solvent placed in the dipping tank after standing are separated, resulting in a reduction in the effective components of the resin impregnated on the fiber, and a rough surface; when the proportion of calcium carbonate is significantly increased, the filler will solidify and block the mold after entering the mold, and some fillers will not be ejected from the mold at the same time as the fiber. The reason is that after the calcium carbonate is solidified, the brittleness is too large, and the bonding internal stress between it and the fiber is less than the friction between the fiber surface and the mold. Therefore, when the mass ratio of the filler components montmorillonite, calcium carbonate, zinc oxide, aluminum hydroxide and silicon dioxide is 2-5:4-6:1-3:4-6:1-3, the generated material can meet the performance requirements as described in the table, meet the relevant requirements for materials used in building envelope systems, and the economy can be optimized.
[0131] 5. By comparing Example 9 with Example 1, it can be seen that when the fineness of montmorillonite is 400-800 mesh, the fineness of calcium carbonate is 400-600 mesh, the fineness of zinc oxide is 400-600 mesh, the fineness of aluminum hydroxide is 400-600 mesh, and the fineness of silicon dioxide is 400-800 mesh, the strength uniformity and appearance of the composite material can be improved. If the filler is too fine, the viscosity of the material will increase and the processing performance will be affected. If the filler is too coarse, the slurry is not easy to disperse evenly, and the finished product will be partially dense and partially loose.
[0132] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A fiber composite material capable of achieving Class A combustion performance, characterized in that: The invention is made of the following raw materials in parts by weight: 60-70 parts of roving, 12-22 parts of filler, 12-18 parts of benzoxazine resin; The benzoxazine resin comprises a benzoxazine monomer and an oxazine catalyst; The structural formula of the benzoxazine monomer is: ; The filler includes montmorillonite, calcium carbonate, zinc oxide, aluminum hydroxide and silicon dioxide; Wherein, the oxazine catalyst is configured to catalyze the curing reaction of the oxazine monomer to release the reaction energy in the system; The R1 includes one of phenyl, alkyl, and aldehyde, the R2 includes one of phenyl, alkyl, and aldehyde, and the number of substitutions of the R2 is one, two, three, or four; The oxazine catalyst includes a phenol catalyst or an imidazole catalyst.
2. A fiber composite material capable of achieving Class A combustion performance according to claim 1, characterized in that: The mass ratio of the benzoxazine monomer to the oxazine catalyst is 5-10:7-8.
3. A fiber composite material capable of achieving Class A combustion performance according to claim 2, characterized in that: The mass ratio of the montmorillonite, calcium carbonate, zinc oxide, aluminum hydroxide and silicon dioxide is 2-5:4-6:1-3:4-6:1-3.
4. The fiber composite material capable of achieving Class A combustion performance according to claim 1, characterized in that: The raw material of the roving includes any one of basalt, carbon fiber and glass or a combination of multiple materials.
5. The fiber composite material capable of achieving Class A combustion performance according to claim 3, characterized in that: The fineness of the montmorillonite is 400-800 meshes, the fineness of the calcium carbonate is 400-600 meshes, the fineness of the zinc oxide is 400-600 meshes, the fineness of the aluminum hydroxide is 400-600 meshes, and the fineness of the silicon dioxide is 400-800 meshes.
6. A method for preparing a fiber composite material capable of achieving Class A combustion performance as claimed in any one of claims 1 to 5, characterized in that: The following steps are involved: S1: Weigh filler and benzoxazine resin, mix and stir, and introduce into a dipping tank; S2: Weigh the untwisted roving and immerse it in a dipping tank to obtain a mixed material after it is fully soaked; S3: The mixed material is subjected to a pultrusion process to obtain a composite material.
7. The method for preparing a fiber composite material capable of achieving Class A combustion performance according to claim 6, characterized in that: Before introducing S1 into the dipping tank, a release agent is applied to the inner wall of the dipping tank.
8. The method for preparing a fiber composite material capable of achieving Class A combustion performance according to claim 7, characterized in that: The release agent accounts for 1-2 wt % of the benzoxazine resin.
9. The method for preparing a fiber composite material capable of achieving Class A combustion performance according to claim 6, characterized in that: In the S3 pultrusion process, the starting temperature is 120°C and the molding temperature is 120°C~200°C.
Citation Information
Patent Citations
Prepreg and fiber reinforced composite material
JP2008056795A
Halogen-free resin composition, and prepreg and laminated board manufactured therefrom
WO2016119356A1